Utilizing open educational practices to support sustainable higher education in the United Arab Emirates - Debolina Halder Adhya; Eesa M. Al Bastaki; Sara Suleymanova; Nasiruddeen Muhammad; Arunprasad Purushothaman (AAOU Journal, 2024)
Purpose – The COVID-19 pandemic has compelled higher education institutions (HEI) in the United Arab Emirates (UAE) and globally to shift to a new pedagogy that is sustainable and resilient to crises and disruptions. It necessitated the integration of technologies as part of pedagogical innovation and modification of higher education practices – advancing toward a more holistic integration of physical and digital tools and methods to enable more flexible, creative, collaborative and participatory learning. In terms of pedagogy, an open approach to learning is essential, combining in-person teaching with technological tools and online learning. Design/methodology/approach – This paper examines theoretical and empirical literature to define the potential benefits of utilizing open educational practices (OEP) in higher education, including better access, furthering equity and enhancing teaching, learning and assessment. Findings – It proposes a comprehensive framework built on a continuum of open pedagogy (OP) that comprises “Emphasis”, “Essentials” and “Evolution”. Based on this framework, a set of recommendations for using OEP for successful knowledge building is provided. Originality/value – The research determined the significance of increased OEP involvement for sustainable learning possibilities and the UAE’s initiatives in developing educators to support innovative pedagogies and technology-enabled teaching-learning standards. The study suggests placing more emphasis on faculty and student scaffolding while using OP for better learning experiences and outcomes, as well as more institutional support and the need for policy development to transform the UAE into a global hub for sustainable education.